Transgender and the Right to Employment in India: Analysing the Trajectories of Discrimination - Utkarsh K. Mishra; Abhishek Negi (Administrative Law Departement Faculty of Law Universitas Sebelas Mare, 2021)
Every citizen of India is guaranteed the right to work under the Indian Constitution. However, policymakers, governments, and the Indian Judiciary have been keen only on laying down a framework concerning right to work. This tendency (un)wittingly affects the minority group—transgender people. In this sense, India currently appears to be lacking a well-defined anti-discrimination employment framework. Regarding this issue, this study aims to investigate the trajectories of transgender community discrimination face in the employment sector. This study is written in the context of human rights discourse analysis. This study argues that although the effort of the Supreme Court and the Government of India has taken a positive step to enhance the livelihood conditions of the transgender communities, it must be mentioned that this recognition is not ample to solve the problem. Although this recognition goes a long way in trying to secure the economic needs of the transgender community, social exclusion takes time to change simultaneously with the changing mindset of society. This Indian Judiciary policy should be followed by the guideline for enforcing the ‘Right to Work,’ especially concerning the transgender community.